In Situ Synthesis of Cu3P/P‐Doped g‐C3N4 Tight 2D/2D Heterojunction Boosting Photocatalytic H2 Evolution†. Issue 2 (10th December 2022) - Hou, Fangyong; Liu, Feng; Wu, Haochen; Qasim, Muhammad; Chen, Yi; Duan, Yang; Feng, Zhibo; Liu, Maochang
Comprehensive Summary: Heterojunction design in a two‐dimensional (2D) fashion has been deemed beneficial for improving the photocatalytic activity of g‐C3 N4 because of the promoted interfacial charge transfer, yet still facing challenges. Herein, we construct a novel 2D/2D Cu3 P nanosheet/P‐doped g‐C3 N4 (PCN) nanosheet heterojunction photocatalyst (PCN/Cu3 P) through a simple in‐situ phosphorization treatment of 2D/2D CuS/g‐C3 N4 composite for photocatalytic H2 evolution. We demonstrate that the 2D lamellar structure of both CuS and g‐C3 N4 could be well reserved in the phosphorization process, while CuS and g‐C3 N4 in‐situ transformed into Cu3 P and PCN, respectively, leading to the formation of PCN/Cu3 P tight 2D/2D heterojunction. Owing to the large contact area provided by intimate face‐to‐face 2D/2D structure, the PCN/Cu3 P photocatalyst exhibits significantly enhanced charge separation efficiency, thus achieving a boosted visible‐light‐driven photocatalytic behavior. The highest rate for H2 evolution reaches 5.12 μmol·h –1, nearly 24 times and 368 times higher than that of pristine PCN and g‐C3 N4, respectively. This work represents an excellent example in elaborately constructing g‐C3 N4 ‐based 2D/2D heterostructure and could be extended to other photocatalyst/co‐catalyst system. Abstract : PCN/Cu3 P 2D/2D heterojunction photocatalyst was prepared by an in‐situ transformation of g‐C3 N4 /CuS 2D/2D heterojunction in a phosphorization treatment and achieved a remarkably enhanced photocatalytic H2 evolution from water splitting.